2012
DOI: 10.5204/jld.v1i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions for blended learning technology: Learners' perspectives

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Students commented that the blend of the programs, enabled them wider and faster access to meaningful curriculum content and instructor support. These findings replicate those of Matheos, Daniel, and McCalla (2005), who note that instructor support in traditional classrooms, is often restricted to specific office times or classroom schedules. Whereas the amount and variety of subject material dit1ered across subjects, many students commented on the degrees of variance in the depth of curriculum materials available on the LMS.…”
Section: Discussionsupporting
confidence: 81%
“…Students commented that the blend of the programs, enabled them wider and faster access to meaningful curriculum content and instructor support. These findings replicate those of Matheos, Daniel, and McCalla (2005), who note that instructor support in traditional classrooms, is often restricted to specific office times or classroom schedules. Whereas the amount and variety of subject material dit1ered across subjects, many students commented on the degrees of variance in the depth of curriculum materials available on the LMS.…”
Section: Discussionsupporting
confidence: 81%
“…This software was essential to the tutorial activities. Research (Matheos et al, 2005;Rose et al, 2000) that has previously found that technological factors relating to having computers and the Internet predict choices may be outdated. Most students in this study had computers and the Internet at home.…”
Section: Discussionmentioning
confidence: 99%
“…Williams and Fardon (2007) reported that Australian university students chose recorded over f2f lectures because of timetable clashes (47%) and outside commitments (43%). Matheos, Daniel, and McCalla (2005) found that having internet connectivity at home was associated with higher access of online resources in a buffet-style computer science course. Learning style was also important.…”
Section: Introductionmentioning
confidence: 99%
“…As Voos () notes, the value added by the blended learning approach is not simply the integration of face‐to‐face and online learning methods, but rather the fundamental reconsideration of course design to maximize new technological possibilities. Our goal was to integrate online components so that they became a natural extension of traditional classroom learning (Matheos, Daniel and McCalla ). We gravitated toward e‐learning technologies such as discussion forums, Wimba Classroom, and Campus Pack Wiki because these allowed us to more realistically recreate the complex and often frustrating process of real‐life environmental negotiation.…”
Section: Debriefmentioning
confidence: 99%